Significance of Sufism in Environmental Sustainability: Eco-Sufism Movement in Islamic Boarding School - Fikri, Fikri Taufiqur Rohman; Zainal Fanani; Kusuma, Danar; Mohammad Fuyudun Niam Imam; Muh. Hafidh Ubaidillah (IJIBS, 2024)
As one of the branches of spirituality in Islam, Sufism emphasizes simplicity, wisdom, and harmony with nature. The Eco-Sufism movement is an approach that integrates Sufi spiritual values with environmental awareness. This study examines the significance of Sufism in environmental sustainability through a case study at the Kanzun Najah Islamic Boarding School, Batu Malang City. This Islamic boarding school has adopted Eco-Sufism-based practices, such as organic farming, utilization of renewable energy, and conservation of natural resources, all inspired by Sufism teachings. Through a qualitative approach, this study analyzes how Sufi teachings on the relationship between humans and nature are translated into concrete actions to support environmental sustainability. The results show that applying Sufi values in environmental management positively impacts the socio-ecological welfare of the Islamic boarding school community while inspiring similar movements in other areas. This study also proposes that Eco-Sufism can comprehensively solve global environmental challenges by strengthening the spiritual connection between humans and nature.